PECULIARITIES OF THE USE OF MARINE CULTURAL SYMBOLS IN THE CREATION OF THE DESIGN OF THE CORPORATE STYLE OF THE BRAND - Pashkevych, K. L.; Wenhui, D.; Petrova, O. V. (Art and Design, 2023)
The purpose of the work is to study the characteristic features of marine style, elements that are used in the design of marine-themed products for further use in the design of brand corporate style. Methodology. The methodological basis of the research is a systematic approach, methods of literary-analytical, systemic-structural, comparative analysis, as well as the historical method. The results. The relationship between symbols of marine culture and brand design based on visual elements such as color and graphics, examined from the perspective of semiotic theory, is explored. With the help of practical cases, the characteristics of marine cultural symbols were analyzed, their spiritual meaning and role in the formation of the design of products in the marine style was investigated, and the ways of using these symbols in the design of the corporate style of brands were studied. It was found that the use of marine style symbols in the design of products related to the theme of the sea (production of products, cafes, restaurants, etc.) adds regional and specific features to the product design, because the concept and awareness of openness and inclusiveness of maritime culture subtly influence consumers. On the example of the design of the restaurant brand "N36°", the perception, application and expression of marine symbols in the design of the corporate style were analyzed and an own design project was developed. It has been established that thanks to the use of abstract expression, simplicity, figurative and plastic characteristics of marine style symbols, it is possible to effectively emphasize the unique advantages and characteristics of the brand. The use of nautical symbolism provides an opportunity to establish an emotional connection between the product and the consumer, as well as spread local culture, thus creating products with marketable value. Scientific novelty. Characteristic symbols of the marine style and their use in the design of corporate style of brands are studied. Practical significance. The results of the research can be used in graphic design for developing a corporate style.